Studies on the Mechanism of Aldehyde Oxidase and Xanthine Oxidase - Alfaro, Joshua F. (2008)
[Image: see text] DFT calculations support a concerted mechanism for xanthine oxidase and aldehyde oxidase hydride displacement from the sp(2) carbon of 6-substituted 4-quinazolinones. The variations in transition state structure show that C-O bond formation is nearly complete in the transition state and the transition state changes are anti-Hammond with the C-H and C-O bond lengths being more product-like for the faster reactions. The C-O bond length in the transition state is around 90% formed. However, the C-H bond is only about 80% broken. This leads to a very tetrahedral transition state with an O-C-N angle of 109 degrees. Thus, while the mechanism is concerted, the anti-bonding orbital of the C-H bond that is broken is not directly attacked by the nucleophile and instead hydride displacement occurs after almost complete tetrahedral transition state formation. In support of this the C=N bond is lengthened in the transition state indicating that attack on the electrophilic carbon occurs by addition to the C=N bond with negative charge increasing on the nitrogen. Differences in experimental reaction rates are accurately reproduced by these calculations, and tend to support this mechanism.